Clinical and Laboratorial Changes in Horses Subjected to a High-Pressure Modified Model of Small Colon Distention - Gravena, Kamila [UNESP]; Hernandez-Tovar, Maria Cristina [UNESP]; Canello, Vinicius Athaydes [UNESP]; Gomide, Lina Maria Wehrle [UNESP]; Bernardi, Nara Saraiva [UNESP]; Martins Dias, Deborah Penteado [UNESP]; Queiroz, Daniela Junqueira [UNESP]; Sabes, Amanda Festa [UNESP]; Lacerda-Neto, José Corrêa [UNESP] (Elsevier, 2016)
The objectives of the study were to study clinical and laboratorial variables of horses subjected to a modified high-pressure model of equine small colon distention. Eight healthy adult horses were subjected to inhalation anesthesia to undergo celiotomy. To perform intraluminal obstruction, the antimesenteric border was incised, and a sterile ball was introduced into the lumen. After the ball was positioned, it was inflated to 80 mm Hg, and the intestinal segment was relocated to the abdominal cavity. After 4 hours of distention, the ball was deflated and removed through a new incision. Blood samples were obtained immediately before anesthetic induction (T0), at the time when the ball was deflated (T4), and at 12-hour intervals during the postoperative period until 76 hours after surgery (T16, T28, T40, T52, T64, and T76). Peritoneal fluid samples were also collected at T0, T4, T16, T28, T52, and T76. Physical examinations were also performed at T0 and every 12 hours for 76 hours subsequently. In this induction model, the ball was not deformed and did not move due to the action of intestinal peristalsis. Leukocytosis was also detected at T16 and T28 (P ≤ .05), mainly due to increased segmented and band neutrophils. In the peritoneal liquid, the total leukocyte count was increased at T16 and remained higher than the count recorded at baseline until T76. Clinically, the animals exhibited systemic inflammatory response syndrome because tachycardia, hyperthermia, and leukocytosis were observed at T16.
Keywords: Colic; Equine; Intraluminal obstruction; SIRS